2012
DOI: 10.1056/nejmcpc1109274
|View full text |Cite
|
Sign up to set email alerts
|

Case 2-2012

Abstract: the Departments of Radiology (V.V.M.) and Pathology (M.N.), Massachusetts General Hospital; and the Departments of Radiology (V.V.M.) and Pathology (M.N.), Harvard Medical School -all in Boston. N Engl J Med 2012;366:259-69. (Internal Medicine): A 63-year-old woman was admitted to this hospital because of rapidly progressive respiratory failure.The patient had a history of Poland syndrome (agenesis of the right breast, pectoralis muscle, and the third and fourth costal cartilages) and had received a silicone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In all experimental groups, the intervention was based on the same three, independent internal medicine cases. Chief complaints in these cases were paraesthesia (first session), fever and respiratory failure (second session) and rapidly progressive respiratory failure (third session) 24–26. Cases were worked through in an iterative approach in different formats: (1) peer-moderated live case discussions in an interactive setting (Live-CCD, n=30), (2) a single-learner format utilising an interactive multimedia platform displaying video recordings of the live case discussions (Video-CCD, n=27) and (3) a single-learner format in which the students worked with the original paper cases of the NEJM (Paper-Cases, n=33).…”
Section: Methodsmentioning
confidence: 99%
“…In all experimental groups, the intervention was based on the same three, independent internal medicine cases. Chief complaints in these cases were paraesthesia (first session), fever and respiratory failure (second session) and rapidly progressive respiratory failure (third session) 24–26. Cases were worked through in an iterative approach in different formats: (1) peer-moderated live case discussions in an interactive setting (Live-CCD, n=30), (2) a single-learner format utilising an interactive multimedia platform displaying video recordings of the live case discussions (Video-CCD, n=27) and (3) a single-learner format in which the students worked with the original paper cases of the NEJM (Paper-Cases, n=33).…”
Section: Methodsmentioning
confidence: 99%
“…This is the only reported case with a history of bilateral reduction mammoplasty, although there are case reports describing an association of augmentation mammoplasty and breast implants with various malignant tumors, including ASB [ 26 - 28 ]. However, a comprehensive review concluded that breast implants are not associated with an increased risk or a delay in detection of breast cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 They are most frequently of skin and soft tissue origin in the head and neck region, but may also arise from other organs such as the liver, spleen, heart, and breast. In particular, angiosarcomas are known to be associated with radiation, 3,4 chronic lymphedema after breast surgery (Stewart-Treves syndrome), 5 and most recently a possible association with silicone breast implants has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat peculiar to angiosarcoma is that it may present with Kasabach-Merritt syndrome, 2,9-14 a consumptive coagulopathy originally described in association with large benign hemangiomas in infants. 15 Pathogenesis is presumably related to platelet trapping within these highly vascular lesions with secondary consumption of clotting factors and resultant bleeding.…”
Section: Discussionmentioning
confidence: 99%